2003
DOI: 10.1242/jcs.00276
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl isomerase Pin1: a catalyst for oncogenesis and a potential therapeutic target in cancer

Abstract: Phosphorylation of proteins on serine or threonine residues preceding proline (Ser/Thr-Pro) is a major intracellular signaling mechanism. The phosphorylated Ser/Thr-Pro motifs in a certain subset of phosphoproteins are isomerized specifically by the peptidyl-prolyl cis-trans isomerase Pin1. This post-phosphorylation isomerization can lead to conformational changes in the substrate proteins and modulate their functions. Pin1 interacts with a number of mitotic phosphoproteins, and plays a critical role in mitoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
152
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(155 citation statements)
references
References 140 publications
(228 reference statements)
2
152
0
1
Order By: Relevance
“…It has been shown that PIN1 is strikingly overexpressed in breast cancer and that its overexpression leads to the upregulation of cyclin D1 and transformation of breast epithelial cells Ryo et al, 2003). As PIN1 is overexpressed in over half of our studied HCC cases, a critical question is whether overexpression of PIN1 has any effect on the cell transformation of hepatocytes.…”
Section: Introduction Results and Discussionmentioning
confidence: 88%
“…It has been shown that PIN1 is strikingly overexpressed in breast cancer and that its overexpression leads to the upregulation of cyclin D1 and transformation of breast epithelial cells Ryo et al, 2003). As PIN1 is overexpressed in over half of our studied HCC cases, a critical question is whether overexpression of PIN1 has any effect on the cell transformation of hepatocytes.…”
Section: Introduction Results and Discussionmentioning
confidence: 88%
“…The prolyl isomerase Pin1 binds to and isomerizes the peptidyl-prolyl bond in specific phosphorylated Ser/Thr-Pro motifs to induce conformational changes in its target proteins (7). These conformational changes can have profound effects on the function of Pin1 substrates, modulating their activity, phosphorylation status, protein-protein interaction, subcellular localization, and stability (16). Interestingly, it was reported that Pin1 regulates SMRT and SRC-3 as downstream effectors of HER-2 signaling (8,17), which is often increased in endocrine-resistant breast tumors and contributes to activate proliferation and/or survival and hormone resistance (6,18).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies indicate that the deregulation might depend on more complex mechanisms, and other members of the pathway may play complementary roles. Recently, peptidyl-proplylisomerase, PIN1, a member of the pathway, has been shown to be upregulated in breast cancer (Wulf et al, 2001;Ryo et al, 2003) and HCCs (Pang et al, 2004). In Pang et al (2004), it was suggested that PIN1 overexpression and mutation of b-catenin were mutually exclusive events, and they both led to accumulation of b-catenin in HCCs.…”
Section: Discussionmentioning
confidence: 99%